TURKISH ATB RELATIVIZATION: IMPLICATIONS ON RELATIVE CLAUSE FORMATION - Meral, Semra Baturay; Meral, Hasan Mesut (DE GRUYTER MOUTON, 2016)
This paper discusses Turkish across-the-board relativization in relation to the two relative clause formation strategies: (i) the empty operator movement analysis of Chomsky (1977), and (ii) the head raising analysis of Kayne (1994). It shows that the across-the-board relative clauses where the head noun is interpreted inside both conjuncts present evidence against the head raising analysis of Turkish relative clauses a la Kayne (1994) due to the fact that ATB relativization does not require that the gaps be in positions requiring the same case. The operator movement analysis of Chomsky (1977), on the other hand, base generates the head noun and renders it free from the case features inside the conjuncts.
Keywords: Across-the-board; relative clauses; case mismatch; head raising; empty operator movement; Linguistics